Resonance properties of quasiperiodic layered structures - Andreev, M.; Borulko, V.; Drobakhin, O.; Sidorov, D. (Видавництво Національного університету "Львівська політехніка", 2009)
Scattering of plane monochromatic waves on quasiperiodic layered structures is considered. Exact solutions for complex amplitudes of reflected and transmitted waves are found by method of transmission matrices. Rigorous and approximate methods are used for determination of complex frequencies of eigen vibration in Bragg structures. Influence of different type of periodicity distortion is investigated. Brewsterization of Bragg reflection in cases of negative values of permittivity and permeability is considered.
Keywords: layered media; Bragg structures; method of transmission matrices; complex frequencies of eigenvibration; metamarerials